Efficient Design to Monitor the Site‐specific Sustained Release of a Non‐Emissive Anticancer Drug. Issue 17 (8th August 2021) - Venu, Parvathy; Le, Trong‐Nghia; Kumar, Pawan; Patra, Diptendu; Kumar, Rajan; Lee, Cheng‐Kang; Rao, N. Vijayakameswara; Shunmugam, Raja
Abstract: A pH‐responsive smart nanocarrier with significant components was synthesized by conjugating the non‐emissive anticancer drug methyl orange and polyethylene glycol derived folate moiety to the backbone of polynorbornene. Complete synthesis procedure and characterization methods of three monomers included in the work: norbornene‐derived Chlorambucil (Monomer 1), norbornene grafted with polyethylene glycol, and folic acid (Monomer 2) and norbornene attached methyl orange (Monomer 3) connected to the norbornene backbone through ester linkage were clearly discussed. Finally, the random copolymer CHO PEG FOL METH was synthesized by ring‐opening metathesis polymerization (ROMP) using Grubbs′ second‐generation catalyst. Advanced polymer chromatography (APC) was used to find the final polymer's molecular weight and polydispersity index (PDI). Dynamic light scattering, scanning electron microscopy (SEM), and transmission electron microscopy (TEM) were utilized to explore the prodrug's size and morphology. Release experiments of the anticancer drug, Chlorambucil and the coloring agent, methyl orange, were performed at different pH and time. Cell viability assay was carried out for determining the rate of survived cells, followed by the treatment of our final polymer named CHO PEG FOL METH. Abstract : Formation of prodrug aggregate in the aqueous environment : A stimuli‐responsive polymer‐drug conjugate with three functional moieties was synthesized. The formed spherical aggregates can be used to efficiently release the non‐emissive anticancer drug chlorambucil with the assistance of polyethylene glycol and folate moieties.